Analysis of Noise Levels in the Engine Room & St. Kernel Using the National Institute for Occupational Safety and Health (NIOSH) Method in PT. Karya Tanah Subur - Agus Samsul Fata; Gaustama Putra (Jurnal Inotera, 2023)
Industry in Indonesia began to show progress and improvement marked by the use of sophisticated machines, almost all production processes in the industry caused noise. Noise can cause damage to hearing devices and cause psychological, physiological disorders that have the potential to cause disruption to work so as to reduce work productivity. PT. Karya Tanah Subur (KTS) is a company engaged in the business of plantation and processing of palm oil, the products produced in the form of crude palm oil (CPO) and kernels. The purpose of this study was to measure the level of noise that occurred in several PT operator rooms. The work of Fertile Land (KTS) which is directly adjacent to the machines that make noise. Then conduct a maximum time analysis of workers exposed to the noise generated based on the NIOSH calculation method. Selected noise sampling is the Engine Room Station (Turbine, Genset) and Kernel Station using the Sound level meter tool. From the results of this study, it shows that both points exceed the Threshold Value (NAB). The longest exposure time is at point 2 with a length of exposure time of 9 hours, while the shortest exposure time is at point 1 with a length of exposure time of 1.2 hours per day. In locations that have a risky noise intensity level, you should use earplugs/earmuffs to minimize the level of noise intensity and other supporting PPE for worker health and safety.